Novel fMRI working memory paradigm accurately detects cognitive impairment in multiple sclerosis. (May 2017) - Nelson, Flavia; Akhtar, Mohammad A; Zúñiga, Edward; Perez, Carlos A; Hasan, Khader M; Wilken, Jeffrey; Wolinsky, Jerry S; Narayana, Ponnada A; Steinberg, Joel L
Background: Cognitive impairment (CI) cannot be diagnosed by magnetic resonance imaging (MRI). Functional magnetic resonance imaging (fMRI) paradigms, such as the immediate/delayed memory task (I/DMT), detect varying degrees of working memory (WM). Preliminary findings using I/DMT showed differences in blood oxygenation level dependent (BOLD) activation between impaired (MSCI, n  = 12) and non-impaired (MSNI, n  = 9) multiple sclerosis (MS) patients. Objectives: The aim of the study was to confirm CI detection based on I/DMT BOLD activation in a larger cohort of MS patients. The role of T2 lesion volume (LV) and Expanded Disability Status Scale (EDSS) in magnitude of BOLD signal was also sought. Methods: A total of 50 patients (EDSS mean ( m ) = 3.2, disease duration (DD) m  = 12 years, and age m  = 40 years) underwent the Minimal Assessment of Cognitive Function in Multiple Sclerosis (MACFIMS) and I/DMT. Working memory activation (WMa) represents BOLD signal during DMT minus signal during IMT. CI was based on MACFIMS. Results: A total of 10 MSNI, 30 MSCI, and 4 borderline patients were included in the analyses. Analysis of variance (ANOVA) showed MSNI had significantly greater WMa than MSCI, in the left prefrontal cortex and left supplementary motor area ( p  = 0.032). Regression analysis showed significant inverse correlations between WMa and T2 LV/EDSS in similar areas ( p  = 0.005, 0.004, respectively). Conclusion: I/DMT-based BOLD activation detects CI in MS. Larger studies are needed to confirm these findings.